Gene Silencing of Sarco/Endoplasmic Reticulum Ca2+-ATPase and NADPH–Cytochrome P450 Reductase as a Novel Approach to Leptinotarsa decemlineata Management - Maribel Mendoza-Alatorre; Tania Samanta Siqueiros-Cendón; Jorge Ariel Torres-Castillo; Sugey Ramona Sinagawa-García; Blanca Flor Iglesias-Figueroa; María Jazmín Abraham-Juárez; Carmen Daniela González-Barriga; Quintín Rascón-Cruz; Luis Ignacio Siañez-Estrada; Edward Alexander Espinoza-Sánchez (Agronomy)
The Colorado Potato Beetle (CPB, Leptinotarsa decemlineata Say, Coleoptera: Chrysomelidae) remains a destructive agricultural pest worldwide that continually overcomes conventional control methods. In recent years, RNA interference (RNAi) has emerged as an alternative for its management; however, although promising results have been reported, its effectiveness has been influenced by several factors, including the length of double-stranded RNA (dsRNA), the delivery method, stability, and especially the selection of the target gene. In this study, we designed and synthesized 290 bp dsRNAs targeting the SERCA and CPR genes from L. decemlineata, which encode the Sarco/Endoplasmic Reticulum Ca2⁺-ATPase and NADPH–Cytochrome P450 Reductase, respectively. Both dsRNAs successfully reduced transcript levels in larvae, with dsSERCA achieving ~60% knockdown by day 3 and dsCPR achieving ~50% knockdown by day 7. Furthermore, both treatments affected the larval growth and survival rate. However, while the dsCPR-treated larvae showed a 59% reduction in weight gain, the administration of dsSERCA had a strong phenotypic effect on the larvae, leading to decreased feeding, a 50.4% reduction in weight gain, and ultimately, 100% mortality. These results suggest that the SERCA and CPR genes could be promising targets for L. decemlineata control and emphasize the importance of appropriate target gene selection for RNAi silencing, as well as the need to explore and validate new genes for RNAi-mediated pest management.